Stations of the Cross at St. Annes Church - Mumbai Archive Project Team (Jio Institute, 2024)
The stations at St. Annes Church represent the route along Via Dolorosa taken by Jesus to reach Mount Calvary, the site of his crucifixion. Commonly, a series of 14 images will be arranged in numbered order along a path, along which worshippers—individually or in a procession—move in order, stopping at each station to say prayers and engage in reflections associated with that station.